On degenerate elliptic equations in Morrey spaces - Francesco Borrello (Le Matematiche, 2006)
Regularity of generalized solutions to degenerate elliptic PDE’s has received a very strong impulse in the direction of finding the minimal assumptions under which regularity results hold true. Definitely, the point of view is that Lebesgue classes are not the right ones where to put lower order terms to ensure regularity.